Valence subbands profile regulation in AlGaN quantum well based on k·p theory. (1st March 2023) - Wang, Xianjun; Jiang, Ke; Sun, Xiaojuan; Zhang, Zi-Hui; Chen, Yuxuan; Wang, Bingxiang; Li, Dabing
Abstract: The profiles for the valence subbands of an AlGaN-based quantum well (QW) is investigated by considering quantum confinement effect (QCE) and strain through the k · p theory. We have found that to increase the QCE and the compressive strain would rise the relative position of the heavy hole (HH) subband to the crystal field splitting hole (CH) subband in the valence band of the QW. However, although the variation trend of the relative valance subbands position is similar, the underlying mechanisms of the modulation by the QCE and strain are not the same. In addition, we have found that if the energy level between the HH and the CH subbands is close at a certain k t point, the subband anti-crossing effect of the QW will enhance their coupling level, causing dipole moments from the conduction subbands to these valence subbands transformation between each other. These results can provide important basis for the active region design of some AlGaN-based short wavelength, high carrier injection, or monolithic integration optoelectronic devices.